2004
DOI: 10.1136/jcp.2003.013946
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma arising from a gastric duplication cyst with invasion to the stomach: a case report with literature review

Abstract: This report describes a rare case of adenocarcinoma arising from a gastric duplication cyst, with invasion to the stomach wall, in a 40 year old Japanese man. A cystic lesion was found between the stomach and the spleen. The cyst had a well circumscribed smooth muscle layer, corresponding to the muscularis propria of the stomach and the mucosa of the alimentary tract. A well differentiated adenocarcinoma was found within the duplication cyst, invading its serosa. Well differentiated adenocarcinoma was independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
98
0
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(110 citation statements)
references
References 7 publications
3
98
0
9
Order By: Relevance
“…Like other pastcasesofGISTs,thepresentcaseproceededwith massivegastricbleedingandrequiredanurgentlaparotomywithlocaltumorresection.Rarely,described cases of gastric bleeding are complex and might be connectedwithanothertypesofgastrictumorsbesides GISTsorGDCoccurringincidentally,simultaneously also with other kind of cancer. The most frequently documentedintheliteraturearesimultaneousoccurrenceofGDCandcancerarisingfromepithelialparts ofduplications.Currently,allpublishedpapersabout ithaveashortreportformasacasedocumentationof differentcancertypeswithGDC.Thelackoforiginal papers indicates substantial rarity of the entity and greatlyrestrictsthepossibilityoffurtherstudies.Barussaudet aldescribedusualgastricadenosquamous carcinomawithinfiltrationofwallGDC [8].Kuraoka et aldescribedasimilarcaseaboutcoincidenceofgastricadenocarcinomawithGDC [9].Hatadescribeda carcinoid tumor arising from the duodenal wall and retroperitoneal GDC. The authors indicated GDC epithelialchangessuchasdysplasiaandanincreased number of neuroendocrine cells, which were probablyprogenitorsofcarcinoid [10].Similarobservations weredescribedbyHorneet alinacaseofneuroendocrinecarcinomawithgastricduplications [11].These rarepublicationshavenotedveryimportantfindings suchasdysplasticchangesofepithelialcellsinGDC A B C D Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Like other pastcasesofGISTs,thepresentcaseproceededwith massivegastricbleedingandrequiredanurgentlaparotomywithlocaltumorresection.Rarely,described cases of gastric bleeding are complex and might be connectedwithanothertypesofgastrictumorsbesides GISTsorGDCoccurringincidentally,simultaneously also with other kind of cancer. The most frequently documentedintheliteraturearesimultaneousoccurrenceofGDCandcancerarisingfromepithelialparts ofduplications.Currently,allpublishedpapersabout ithaveashortreportformasacasedocumentationof differentcancertypeswithGDC.Thelackoforiginal papers indicates substantial rarity of the entity and greatlyrestrictsthepossibilityoffurtherstudies.Barussaudet aldescribedusualgastricadenosquamous carcinomawithinfiltrationofwallGDC [8].Kuraoka et aldescribedasimilarcaseaboutcoincidenceofgastricadenocarcinomawithGDC [9].Hatadescribeda carcinoid tumor arising from the duodenal wall and retroperitoneal GDC. The authors indicated GDC epithelialchangessuchasdysplasiaandanincreased number of neuroendocrine cells, which were probablyprogenitorsofcarcinoid [10].Similarobservations weredescribedbyHorneet alinacaseofneuroendocrinecarcinomawithgastricduplications [11].These rarepublicationshavenotedveryimportantfindings suchasdysplasticchangesofepithelialcellsinGDC A B C D Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Due to malignant transformation and a previous report of gastric cancer arising in duplications of the stomach, surgical excision is considered to be the best treatment [9]. Complete resection of the cyst is the ideal technique for treatment [10].…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological criteria for diagnosis of gastric duplication cyst include the wall of the cyst being contiguous with the stomach wall, the presence of smooth muscle surrounding the cyst and in continuation with the gastric musculature, and lining of the cyst wall by epithelial, gastric, or gut mucosa of any type [4][5][6][7][8]. Volume 5 Issue 7 -2016 CT imaging can precisely define location, size, and local tissue involvement.…”
Section: Discussionmentioning
confidence: 99%